In Situ Generation of Electrolyte inside Pyridine‐Based Covalent Triazine Frameworks for Direct Supercapacitor Integration. Issue 12 (11th May 2020) - Troschke, Erik; Leistenschneider, Desirée; Rensch, Tilo; Grätz, Sven; Maschita, Johannes; Ehrling, Sebastian; Klemmed, Benjamin; Lotsch, Bettina V.; Eychmüller, Alexander; Borchardt, Lars; Kaskel, Stefan
Abstract: The synthesis of porous electrode materials is often linked with the generation of waste that results from extensive purification steps and low mass yield. In contrast to porous carbons, covalent triazine frameworks (CTFs) display modular properties on a molecular basis through appropriate choice of the monomer. Herein, the synthesis of a new pyridine‐based CTF material is showcased. The porosity and nitrogen‐doping are tuned by a careful choice of the reaction temperature. An in‐depth structural characterization by using Ar physisorption, X‐ray photoelectron spectroscopy, and Raman spectroscopy was conducted to give a rational explanation of the material properties. Without any purification, the samples were applied as symmetrical supercapacitors and showed a specific capacitance of 141 F g −1 . Residual ZnCl2, which acted formerly as the porogen, was used directly as the electrolyte salt. Upon the addition of water, ZnCl2 was dissolved to form the aqueous electrolyte in situ. Thereby, extensive and time‐consuming washing steps could be circumvented. Abstract : Just add water : A series of covalent triazine frameworks and derived carbonaceous materials based on 3, 5‐dicyanopyridine is developed. These materials, which still contain ZnCl2 crucial for the synthesis, are further applied as supercapacitors. The electrolyte is thereby generated in situ by adding water to the electrode set‐up.